EKSTRAKSI DAN STABILITAS ZAT PEWARNA ALAM DARI KATUL BERAS KETAN HITAM (Oryza sativa glutinosa) EXTRACTION AND STABILITY OF NATURAL COLORANT FROM RED GLUTINOUS RICE BRAN (Oryza sativa glutinosa) - Tirza Hanum (Jurnal Teknologi dan Industri Pangan, 2000)
Three extraction methods were studied to isolate natural colorant from red glutinous rice bran. Stability of extracts in relation to processing conditions and in the model beverages was determined at room temperature. Identifications of anthocyanidins was performed using reversed phase HPLC. Extraction method using acidified methanol solvent showed the highest yield (260,24 ±28,64 mg/100g). HPLC patern indicated the presence of six major anthocyanidins, two of them were identified as apigenidin and apigenin. Stability of anthocyanin colorant was higher in a lower acid condition and was reduced to the lowest  value of 49,4, 65,4, 40,8 and 36,6% by high temperature, UV light, sunlight, and the presence of oxidator agent. respectively. Retention of antocyanin in tanin and ascorbic acid added into the model beverages was lower than  in  protein containing beverage  or control.